A grayanotox-9(11)-ene derivative from Rhododendron brachycarpum and its structural assignment via a protocol combining NMR and DP4 plus application. (January 2017) - Tuan, Nguyen Quoc; Oh, Joonseok; Park, Hyun Bong; Ferreira, Daneel; Choe, Sanggil; Lee, Juseon; Na, MinKyun
Abstract: A growing body of evidence points to the useful roles of computational approaches in the structural characterization of natural products. Rhododendron brachycarpum has been traditionally used for the control of diabetes, hepatitis, hypertension, and rheumatoid arthritis and classified as an endangered species in Korea. A grayanotox-9(11)-ene derivative along with five known diterpenoids, were isolated from the MeOH extract of R. brachycarpum . Extensive 1D and 2D NMR experiments were conducted to establish the 2D structure and relative configuration of the grayanotox-9(11)-ene derivative. Comparison of simulated and experimental ECD spectra resulted in an inconclusive outcome to assign its absolute configuration. Alternatively, gauge-including atomic orbitals (GIAO) NMR chemical shift calculations, with support by the advanced statistical method DP4 plus, and acid hydrolysis were employed to establish its absolute configuration. This work exemplifies how NMR analysis, combined with quantum mechanics calculations, is a viable approach to accomplish structural assignment of minor abundance molecules in lieu of X-ray crystallography or chiroptical approaches. Graphical abstract: This work delineates how NMR analysis combined with DP4 plus can be utilized to achieve structural assignment in lieu of X-ray crystallography or chiroptical approaches. Highlights: The DP4 plus approach is a viable tool in accomplishing full structural assignment. The study demonstrates how chemistry can be uncovered in endangered plant species. The research may justify the conservation of endangered plant species.